Determination Model of Housing Purchase Decision with Sharia System without Bank - Sihotang, Mutiah Khaira; Hasanah, Uswah; Nst, Salman (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
Housing is a primary need that must be fulfilled. The choice of a comfortable place to live is a dream for every family. Seeing this fact, developers are trying to meet the needs of the community in various ways. Currently, Islamic housing is one of the potential businesses due to the high demand for this. The high demand for Islamic housing shows that people's financial literacy is getting better. The community seriously wants to stay away from usury practices including home ownership. This study aims to determine the determination of non-bank Islamic housing purchase decisions. The dependent variable used in this study is price. Residential environment, religiosity, and housing quality. The sampling method used is the saturated sample method or total sampling, namely, all populations are sampled. The number of samples in this study was 112 people. In this study, multiple linear regression tests were carried out. Before performing multiple regression, classical assumption tests and data quality tests were first carried out. All test stages and data analysis were carried out with the help of SPSS. The results of this study state that the variables of housing environment, religion, and housing quality have a significant effect on purchasing decisions for housing with a non-bank Islamic system. While the price variable has no significant effect on the decision to purchase housing with a non-bank sharia system. This can be seen from the t test with a significance value > 0.05. Future research is expected to be able to expand the range of variables and make research even better because the demand for sharia housing without banks is increasing.